USE OF MULTI-CRITERIA METHOD EDAS IN RANKING EMPLOYMENT TOURISM INDUSTRY CANDIDATES WITH INTRODUCTION OF CORRECTIVE STEP - Štilić, Anđelka; Nicić, Miloš; Zimonjić, Borko; Njeguš, Angelina (The Business of Tourism, 2019)
The aim of this paper is to present a relatively new method of multi-criteria analysis -EDAS and to demonstrate its use in ranking employment candidates in the tourism industry. An example of the use of the EDAS method outlined here is authentic; wider segment of the survey and use of real data and requirements led to real problems and in order to solve them, extension of EDAS was developed:  EDAS+; that was tested and yielded satisfactory results.